Chief and Copper - G.F. MacDonald Collection (1972)
Hereditary Gitxsan chief, David Gunanoot. David is the son of famous fugitive and folk hero, Simon Gunanoot who evaded RCMP and Pinkerton men for 13 years and was later aquited of the charges. His father's story is told in a book by David Ricardo Williams, Trapline Outlaw: Simon Peter Gunanoot. In this picture David holds the White Owl Copper made by Earl Muldo of Kispiox.